Emotional Well-Being Matters Most: How Job Flourishing Reduces Quiet Quitting Among Generation Z In Indonesia - Narendra, Zahra Audia; A’yuninnisa, Rizqi Nur’aini (Universitas Andalas, 2025)
The post-pandemic work culture has undergone significant changes, particularly in work arrangements, with Generation Z being the most affected as they enter the workforce. Amidst the shift, a new phenomenon called Quiet Quitting emerges, threatening the workforce’s productivity through its detrimental effects. This study examined the relationship between job flourishing and quiet quitting tendency among Generation Z employees in Indonesia. Grounded in Social Exchange Theory, the research argues that higher levels of job flourishing are associated with a lower tendency to engage in quiet quitting. A quantitative approach was employed, using purposive sampling and online questionnaires. This study collected 166 respondents from Gen Z employees across Indonesia. The results revealed a significant negative association between job flourishing and quiet quitting. Among the dimensions of job flourishing, emotional well-being was found to have the strongest effect on reducing the quiet quitting tendency. These findings offer valuable insights for organisations and policymakers in developing strategies to foster job flourishing as a means to mitigate quiet quitting and enhance workforce productivity.